MODEL KOLABORASI PEMERINTAH DALAM PENANGANAN BENCANA ALAM (STUDI KASUS: KOLABORASI PEMERINTAH DAERAH DENGAN KOREM 061/SURYAKENCANA) - Faisol Izuddin Karimi; Agus Subagyo; Dadan Kurnia (Universitas Jenderal Ahmad Yani, 2026)
This study stems from the complexity of disaster impacts, which necessitates cross-institutional collaboration capable of integrating organisational resources and capacities. The study aims to analyse the model of collaboration between the local government and Korem 061/Suryakancana in the management of natural disasters, as well as to identify the factors that support the effectiveness of this collaboration. This study employs a qualitative approach using a case study design. Data were collected through in-depth interviews with informants from the local government, the Regional Disaster Management Agency (BPBD), and personnel from Korem 061/Suryakancana, supplemented by field observations and document analysis. Data analysis was conducted interactively through the stages of data reduction, data presentation, and drawing conclusions. The research findings indicate that collaboration between the local government and Korem 061/Suryakancana takes place through structured coordination mechanisms, primarily via disaster coordination forums and emergency response command posts. The local government acts as the main coordinator, whilst the Military Command provides operational support such as the evacuation of victims, the distribution of logistics, and the construction of emergency facilities. These findings underscore the importance of synergy between civilian and military actors in strengthening disaster response capacity at the local level, as well as promoting the strengthening of cross-institutional coordination mechanisms in disaster management.